Experimental composite containing silicon dioxide-coated silver nanoparticles for orthodontic bonding: Antimicrobial activity and shear bond strength - Rogéria Christina de Oliveira AGUIAR; Larissa Pereira NUNES; Eduardo Silva BATISTA; Marina Mariante VIANA; Marcela Charantola RODRIGUES; Bruno BUENO-SILVA; Marina Guimarães ROSCOE (Dental Press Editora, 2022)
ABSTRACT Objective: This study aimed to investigate the antimicrobial activity and shear bond strength (SBS) of orthodontic brackets to bovine enamel using experimental composites with different concentrations of silicon dioxide-coated silver nanoparticles (Ag@SiO2 NPs). Methods: Fifty bovine incisors were divided into five groups according to the composite (n = 10): G1 - Control Group (Transbond XT Resin), G2 - Experimental composite without Ag@SiO2 NPs; G3 - Experimental composite with 0.5% of Ag@SiO2 NPs; G4 - Experimental composite with 1% of Ag@SiO2 NPs; G5 - Experimental composite with 3% of Ag@SiO2 NPs. The SBS test was performed using a universal mechanical testing machine, and the adhesive remnant index (ARI) was analyzed by optical microscopy. For the antimicrobial activity evaluation, Streptococcus mutans (S. mutans) biofilm was formed for three days in hydroxyapatite discs. Posteriorly, S. mutans colony forming units (CFU) were evaluated. For SBS analysis, Analysis of Variance was used, followed by the Tukey test, at a 5% statistical significance level. The CFU data were analyzed by Kruskal-Wallis, followed by Dunn as a post-hoc test. The ARI results were analyzed descriptively. Results: There was no statistically significant difference in SBS values between the experimental and control groups (p>0.05). A 3% incorporation of Ag@SiO2 NPs statistically reduced the SBS values (p<0.05) compared to the 1% group. The addition of 3% of Ag@SiO2 NPs to the composites significantly reduced S. mutans biofilm formation, compared to group G2 (p<0.05). Conclusion: Composites incorporating 3% of Ag@SiO2 NPs presented similar SBS values compared to the control group, and showed significant antimicrobial activity.